EARTHQUAKE’S INSURABILITY - Robey, Christopher J. (Assurances, 1999)
In the following pages, Mr. Robey introduces his subject by saying that we know the earthquake event will occur and will cause important damage, but we do not know when it will happen. Because we know its realisation, we can keep the damage to a minimum. Since we know for sure that the earthquake will happen, cushioning the economic impact and speeding recovery afterwards are just as important, and this is where the insurance industry comes in. The author retraces the origin of protection against earthquake. He explains that the trouble with earthquake insurability is determining a scientific model, making that catastrophe event difficult to be rated and to be transferred to the reinsurance market. He is questionning what the insurance industry does after such an event and also the role il can play in loss mitigation.